Perceptions of celebrity athletes involved in social cause endorsement - Biz, Manuela; Schubert, Mathias (Frontiers in Sports and Active Living, 2024)
Due to their ability to evoke unique associations in people's minds, professional athletes are considered prime ambassadors for companies, brands or organisations to add intangible values, credibility and awareness to their products or services. Based on that premise, using celebrity athletes for supporting social causes has also become a frequent practice over the past years. Empirical knowledge on how such activities are being perceived by involved athletes is scarce. Little is known about what they consider to be relevant attributes of their personal brand that make them suitable for endorsing social causes. Based on semi-structured interviews with (n=12) current and recently retired professional athletes from four different continents, we explore the most prominent attributes of athlete brands as well as other important features in that regard. Our results indicate that, in contrast to product endorsement, on-field attributes of the athlete brand are considered more important in relation to social causes. Our study is useful for a variety of stakeholders, such as athletes or organisations considering getting involved in social cause endorsement.